Covishield vaccine experience in a health care setting - Boorugu, Hari Kishan; Misra, Krushna Chandra; Prusty, B. Saroj Kumar (International Journal of Research in Medical Sciences, 2021)
Background: SARS-CoV-2 pandemic has affected the whole world and India is one among the most affected countries. Vaccination is the most important tool to halt this pandemic and vaccine hesitancy unfortunately derails vaccination drive. Vaccine hesitancy among people is mainly due to concerns about vaccine safety! This study was done to assess adverse effects of Covishield vaccine among health care workers in a single health care organization. Methods: All the vaccine recipients were requested to answer a questionnaire with demographic details and various side effects following both the doses of Covishield vaccination. Results: About 665 employees responded to the questionnaire and the most common adverse reaction following Covishield vaccine was injection site pain, which was reported by 63% of vaccinees after first dose of vaccine. Conclusions: Covishield vaccine is relatively safe and incidence of major adverse events are rare following vaccination.